AESTHETIC MEDICINE IN GYNECOLOGY: REVIEW OF SELECTED METHODS - Patrycja Misiaszek,; Szymon Rydzewski,; Sylwia Boczek,; Mikołaj Herba,; Patrycja Kinga Marta, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Aesthetic gynecology is a rapidly evolving branch of medicine that integrates aesthetic, functional, and psychosexual aspects of women’s intimate health. Procedures within this field aim not only to improve the appearance of the external genitalia but also to address symptoms of genitourinary syndrome of menopause (GSM), urinary incontinence, sexual dysfunction, and postpartum or oncological changes.Aim: The aim of this study was to provide a comprehensive review of selected aesthetic procedures used in gynecology, with a focus on their indications, mechanisms of action, efficacy, and safety, as well as the psychological and ethical aspects surrounding their use.Materials and Methods: This work was based on a narrative literature review. Sources included peer-reviewed medical journals, systematic reviews, meta-analyses, and current clinical guidelines from both Polish and international databases. The selection criteria prioritized recency, clinical relevance, and scientific credibility.Results: The review revealed a wide range of procedures available in aesthetic gynecology, including injectable treatments, energy-based therapies, surgical techniques, and supportive care. Most procedures were found to be safe and well tolerated, with high levels of patient satisfaction. They demonstrated benefits in improving both physical symptoms and psychosocial well-being, particularly in postmenopausal and postpartum women. However, limitations include the lack of standardized protocols and long-term outcome data for some methods.Conclusions: Aesthetic gynecology holds significant therapeutic and psychological value, especially when applied within a multidisciplinary, individualized care model. Ethical practice requires proper patient qualification, informed consent, and education regarding both risks and realistic expectations. Further research and professional training are essential to ensure safe, evidence-based implementation of these procedures.